The Identification of Effect on Training, Competency and Building Quality in Malaysian Construction Project - Eizzaty Sohimi, Nurul; Mohd Affandi, Haryanti; Hassan, Fadzil; Bekri Abdul Rahim, Mohd; Abdul Wahab, Norwaliza (International Journal of Engineering and Technology, 2018)
Competency has been recognized as one of the critical factors that affected the building quality in a construction project. Furthermore, one of the methods to develop and enhance the competency of the employees is through training. However, training has to meet the knowledge and skills that required by the employees to ensure the training does enhance the employee's competency level.  This study aims to investigate the training problem and effect toward the building quality of construction project. The data were obtained from literature reviews, focus groups, and a semi-structured interview. Focus groups and semi-structured interviews had been held involving 20 site supervisor and 5 site supervisor from the Selangor State Development Corporation. The results show that the training affects the competency in producing a high quality of building construction project. However, there is a problem in training such as the incompetence of the trainer, mismatches between the training offered and the organization failed to identify the training needs of the workers. Thus, future study is suggested for identifying training needs by the construction practitioner in construction quality training.